Mixed-mode fracture in open-hole composite plates of finite-width: An asymptotic coupled stress and energy approach. (September 2017) - Felger, J.; Stein, N.; Becker, W.
Abstract: In the present work, brittle failure of finite-width composite plates containing a circular hole under uniaxial tension loading is investigated using a coupled stress and energy criterion within the framework of finite fracture mechanics. Depending on the material anisotropy, the onsets of symmetric and antisymmetric crack patterns are investigated considering mixed-mode fracture. In order to provide an efficient finite fracture mechanics analysis, a semi-analytical approach is proposed combining the method of complex potentials with a two-scale asymptotic solution procedure. Within the asymptotic framework, higher-order terms and the application of Padé approximation are implemented allowing for an extended applicability of asymptotic solutions. In addition, full-numerical analyses are performed and the accuracy of the asymptotic approach, in particular with regard to the finite-width, is thoroughly examined. The effects of hole size and fibre orientation on the plate's effective strength are studied using the proposed finite fracture mechanics approach and theoretical strength predictions are compared to experimental results from literature.